Early-strength delayed coagulation type concrete admixture and preparation method thereof

By constructing an 'interfacial microreactor' system of diethylene glycol monovinyl ether, nano-calcium carbonate, and triallyl citrate, the technical contradiction between retarding and early strength of polycarboxylate superplasticizers was resolved. This achieved a synergistic effect of retarding and early strength in concrete, simplified the preparation process, addressed technical issues, and realized a synergistic effect of retarding and early strength during cement hydration. It also solved the problem of poor compatibility between retarder and PCE in existing technologies, and improved the fluidity and early strength of concrete.

CN121021033APending Publication Date: 2025-11-28SHANDONG VOCATIONAL COLLEGE OF LIGHT IND
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202511528089.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-10-24
Publication Date
2025-11-28

AI Technical Summary

Technical Problem

Existing polycarboxylate superplasticizers, while improving the fluidity retention of concrete, tend to delay the cement setting process, resulting in slow early strength development of concrete and affecting project progress. At the same time, the retarders have poor compatibility with PCE, the system is prone to decay, and problems such as segregation and delayed bleeding can occur.

Method used

An interfacial microreactor system was constructed by molecular design, consisting of diethylene glycol monovinyl ether, nano-calcium carbonate, and triallyl citrate. Using nano-calcium carbonate as an in-situ catalytic center, the retarding effect of citric acid was precisely controlled, and it was seamlessly converted into an early-strength crystal nucleus during the hydration process, achieving a synergistic effect of retarding and early strength.

Benefits of technology

It achieves the extension of concrete workability retention time and simultaneous improvement of early and late strength, avoids disordered release of retarders and early strength lag, improves concrete fluidity and early strength, and simplifies the preparation process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention belongs to the technical field of concrete, and particularly relates to an early-strength delayed-coagulation concrete admixture and a preparation method thereof. The early-strength delayed-coagulation concrete admixture is prepared from an unsaturated acid monomer, an unsaturated polyether macromonomer, an unsaturated citrate monomer, an unsaturated diethylene glycol monomer, a reducing agent, an initiator, a chain transfer agent, a solubilizer, deionized water and nano calcium carbonate. Wherein the unsaturated citrate monomer is triallyl citrate, and the unsaturated diethylene glycol monomer is diethylene glycol monovinyl ether. According to the invention, the workability retention time of the fresh concrete is effectively prolonged, and normal development of early and later strength of the concrete can be guaranteed.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application belongs to the technical field of concrete, and particularly relates to an early-strength and retarding-type concrete admixture and a preparation method thereof. BACKGROUND

[0002] With the rapid improvement of the technical level of the construction industry and the continuous expansion of infrastructure construction, the requirements of various projects on the performance of concrete are also increasingly diversified. In recent years, polycarboxylate superplasticizer (PCE) has become an important technical approach to improve the overall performance of concrete due to its excellent water-reducing rate, low dosage characteristics, and advantages such as flexible molecular design and environmental friendliness. However, in special projects such as steel pipe concrete construction requiring long-term fluidity or super high-rise buildings requiring long-distance pumping, the loss of the workability of freshly mixed concrete over time is increasingly significant. At this time, it is difficult to meet the actual construction requirements by relying only on the water-reducing function of PCE, and it is necessary to further improve its dispersion and retention ability of cement particles. In order to enhance the continuous retention effect of PCE on the workability of freshly mixed concrete, PCE is often used in combination with sodium gluconate, sucrose, sodium hexametaphosphate and other retarding components in engineering to maintain the fluidity of concrete by delaying the cement hydration process. However, this method has the disadvantages of poor compatibility between retarding agents and PCE, easy corruption of the system, and may also cause a series of adverse effects such as concrete segregation, delayed bleeding and slow strength development.

[0003] In order to avoid the problems caused by the combination of conventional PCE and retarding agents, researchers turn to directly synthesize polycarboxylate superplasticizers with retarding function through molecular design. Chinese patent CN119038897A discloses a super-retarding polycarboxylate superplasticizer and its preparation method and application, which uses isopentenyl polyoxyethylene ether, modified acrylic acid, hydroxyethyl acrylate phosphate and modified N,N-dimethyl(methacryloxyethyl) amine propyl sulfonate inner salt as raw materials, and successfully prepares a super-retarding PCE which shows good workability retention ability in concrete. Chinese patent CN119371608A discloses a retarding polycarboxylate superplasticizer and its preparation method, which uses unsaturated polyether monomer, quaternary ammonium salt cation monomer, unsaturated sulfonate monomer, unsaturated phosphate monomer, unsaturated hydroxyl fatty acid ester monomer and acrylic acid as reaction raw materials, and synthesizes a retarding polycarboxylate superplasticizer suitable for high temperature environment, which effectively guarantees the construction performance of concrete under high temperature conditions. However, the retarding PCE in the above patents often significantly delays the cement setting process while improving the fluidity retention of concrete, resulting in slow development of early strength of concrete and adversely affecting the project progress. SUMMARY

[0004] The application aims to provide an early-strength and slow-setting concrete additive which can effectively prolong the workability retention time of fresh concrete and guarantee the normal development of early and late strength of the concrete.

[0005] The early-strength and slow-setting concrete additive is prepared from unsaturated acid monomer, unsaturated polyether macromonomer, unsaturated citrate monomer, unsaturated diethylene glycol monomer, reducing agent, initiator, chain transfer agent, solubilizing agent, deionized water and nano calcium carbonate.

[0006] The unsaturated acid monomer is acrylic acid.

[0007] The unsaturated polyether macromonomer is iso-pentenyl polyoxyethylene ether or methyl allyl polyoxyethylene ether. The iso-pentenyl polyoxyethylene ether has the following structural formula:

[0008] In the formula, n1 is 25-75. The methyl allyl polyoxyethylene ether has the following structural formula:

[0009] In the formula, n1 is 25-75.

[0010] The molar ratio of the unsaturated acid monomer, the unsaturated polyether macromonomer, the unsaturated citrate monomer and the unsaturated diethylene glycol monomer is 2.5-3.2:1:0.2-0.3:0.4-0.6.

[0011] The reducing agent is sodium bisulfite or chalk, the mass ratio of the reducing agent and the initiator is 0.6-0.8:1; the initiator is one of sodium peroxide, ammonium persulfate and hydrogen peroxide, the amount of the initiator is 1.6-2.2% of the total mass of the unsaturated acid monomer, the unsaturated polyether macromonomer, the unsaturated citrate monomer and the unsaturated diethylene glycol monomer; the chain transfer agent is mercaptoacetic acid or mercaptoethanol, the amount of the chain transfer agent is 1.2-1.8% of the total mass of the unsaturated acid monomer, the unsaturated polyether macromonomer, the unsaturated citrate monomer and the unsaturated diethylene glycol monomer.

[0012] The solubilizing agent is ethanol, the mass ratio of the solubilizing agent and the unsaturated citrate monomer is 1-2:1; the average particle size of the nano calcium carbonate is 50-75 nm.

[0013] The preparation method of the early-strength and slow-setting concrete additive comprises the following steps: (1) unsaturated polyether macromonomer is dissolved in deionized water to obtain a bottom solution, the bottom solution is heated to obtain a preheated bottom solution; unsaturated acid monomer, unsaturated citrate monomer, unsaturated diethylene glycol monomer, reducing agent, chain transfer agent, solubilizer and deionized water are mixed to obtain solution A; initiator is dissolved in deionized water to obtain solution B; (2) solution A and solution B are simultaneously added to the preheated bottom solution to react, after the addition is completed, the reaction is kept, the temperature is lowered, liquid alkali is added to adjust the pH, and deionized water is added to dilute, to obtain a polycarboxylic acid water reducing agent solution; (3) nano calcium carbonate is added to the polycarboxylic acid water reducing agent solution and stirred to obtain an early strength and slow setting type concrete admixture.

[0014] In step (1), the mass concentration of the bottom solution is 50-60%, the heating temperature is 35-50℃; the mass concentration of solution A is 28-35%, and the mass concentration of solution B is 1-3%.

[0015] In step (2), the dropping time of solution A is 3-3.5 hours, the dropping time of solution B is 3.5-4.0 hours; the reaction temperature is 35-50℃, the reaction temperature is kept at 35-50℃, the reaction time is kept for 1-1.5 hours; the temperature is lowered to below 30℃, the pH is adjusted to 7-8; the solid content of the polycarboxylic acid water reducing agent solution is 20-25wt.%.

[0016] In step (3), the mass ratio of the polycarboxylic acid water reducing agent solution to nano calcium carbonate is 1:0.4-0.5, the stirring temperature is 20-30℃, and the stirring time is 0.5-1.0h.

[0017] When the early strength and slow setting type concrete admixture of the application is applied to concrete, the dosage is calculated according to the amount of polycarboxylic acid water reducing agent solution in the concrete admixture, which is 0.3-0.5% of the total mass of cementitious materials.

[0018] The application constructs a "interface micro-reactor" system tightly coupled by diethylene glycol monovinyl ether, nano calcium carbonate and citric acid triallyl ester through the ingenious design of molecular chain segments. The system realizes seamless connection and mutual promotion of slow setting and early strength in the cement hydration process, and the synergistic mechanism can be divided into two closely related stages: First stage: synergistically constructed "interface micro-reactor" and its precise slow setting effect Firstly, the diethylene glycol monovinyl ether group plays a key role of "structure organizer". With its unique hydrophobic interfacial activity, it will preferentially adsorb and coat the surface of nano calcium carbonate particles in the blending step after polymer synthesis, like a "molecular gripper", firmly "linking" nano calcium carbonate to the polycarboxylic acid molecular chain. This not only solves the problem of easy agglomeration of nanoparticles in the strong alkaline and high ionic concentration cement slurry, but more importantly, it builds a structural foundation: a three-dimensional composite structure with nano calcium carbonate as the core, polycarboxylic acid molecular chain as the carrier, and citric acid triallyl ester groups surrounding the periphery. The citric acid triallyl ester group has been polymerized into the polycarboxylic acid molecular structure, and the polycarboxylic acid realizes physical adsorption of nano calcium carbonate through the diethylene glycol monovinyl ether group in the molecular structure. The citric acid triallyl ester group is thus passively and firmly "surrounded" around the periphery of the nano calcium carbonate particles.

[0019] When the additive enters the concrete, the whole composite structure relies on the carboxyl group in the polycarboxylic acid molecule to adsorb on the surface of the cement particles, and plays a dispersing role through the polyoxyethylene side chain. At this time, the synergistic retarding mechanism is activated: (1) Local catalytic hydrolysis: the surface of nano calcium carbonate is rich in alkaline sites and calcium sites. It is no longer just an inert early strength component, but has been transformed into an in-situ catalytic center. The citric acid triallyl ester group "fixed" near the nano calcium carbonate (both diethylene glycol monovinyl ether group and citric acid triallyl ester group are polymerized into the same polycarboxylic acid molecular structure, when the diethylene glycol monovinyl ether group adsorbs on the nano calcium carbonate, the citric acid triallyl ester group is naturally "fixed" near the nano calcium carbonate), its hydrolysis reaction will be locally catalyzed by the surface of nano calcium carbonate, making the release of citric acid more concentrated and efficient at the cement-water interface, rather than randomly in the liquid phase. (2) Microenvironment regulation: the hydrophobicity of the diethylene glycol monovinyl ether group creates a unique interfacial microenvironment on the nanoscale, which can regulate the activity of water molecules and the concentration of hydroxyl ions around the ester group, making the hydrolysis rate of citric acid triallyl ester group more stable and controllable, avoiding the "instantaneous excess" release of the retarder citric acid (citric acid triallyl ester is a "retarder precursor", it slowly releases the real "retarder" citric acid through hydrolysis reaction), thus realizing real "precise retarding".

[0020] Second stage: seamless functional conversion from "reactor" to "crystal nucleus" As the hydration process progresses, and the hydrolysis of the triallyl citrate groups is largely complete, the retarding effect gradually weakens, revealing the synergistic advantages of this system once again. The nano-calcium carbonate, previously the core of the "catalytic reactor," is now highly dispersed due to the diethylene glycol monovinyl ether groups and firmly positioned on the surface of the cement particles. At this point, it can be converted in situ into the most efficient "nucleation seeds" without delay or diffusion. Hydrated calcium silicate (CSH) gel immediately and rapidly forms and grows from these highly active nano-seeds, significantly accelerating the cement's structural formation process.

[0021] In summary, the three components form an organic whole: diethylene glycol monovinyl ether acts as the structural link, elevating nano-calcium carbonate from a simple early-strength agent to a catalytic core for the retarding reaction; nano-calcium carbonate, in turn, provides an in-situ catalytic platform for triallyl citrate, ultimately achieving a seamless functional transformation into an early-strength crystal nucleus. It is precisely this interlocking and mutually reinforcing synergistic effect that achieves the breakthrough effect of simultaneously optimizing both retarding and early-strength properties.

[0022] The beneficial effects of this invention are as follows: (1) It achieves synergistic effect of slow setting and early strength, fundamentally solving the performance contradiction between the two.

[0023] Existing technologies often balance retarding and early strength through simple physical compounding, but the effects are limited and often accompanied by performance sacrifices. This invention, through molecular design, constructs an "interfacial microreactor" system coupling diethylene glycol monovinyl ether, nano-calcium carbonate, and triallyl citrate. This system transforms the retarding and early strength components from independent units into an organic whole at the molecular level, with interconnected components. This seamlessly transforms the end point of the retarding process into the most efficient starting point of the early strength process, thus achieving a synergistic effect of "1+1+1>3".

[0024] (2) It greatly improves the utilization efficiency and accuracy of the retarder citric acid, and achieves precise retarding.

[0025] This invention utilizes nano-calcium carbonate as an in-situ catalytic center to precisely confine the hydrolysis reaction of triallyl citrate to the cement particle-water interface, avoiding the disordered and inefficient consumption of the retarder citric acid in the liquid phase. Simultaneously, the interfacial microenvironment constructed by the diethylene glycol monovinyl ether groups regulates the hydrolysis rate, achieving a stable and continuous release of the retarder citric acid. This effectively avoids the technical problem of severely delayed early strength development of concrete caused by "instantaneous excess" of the retarder citric acid.

[0026] (3) It endows the early strength component with dual functions, ensuring the rapid growth of early strength.

[0027] In this invention, nano-calcium carbonate initially acts as a "catalytic reactor" for the retarding reaction, and later transforms into a highly efficient "nucleation seed" in situ. Due to the "linking" effect of the diethylene glycol monovinyl ether group, nano-calcium carbonate remains highly dispersed and anchored on the surface of cement particles. Once the retarding effect ends, it can immediately and without delay induce the formation of hydration products, greatly accelerating the structure formation and fundamentally overcoming the inherent defect of traditional retarding admixtures that inevitably lead to early strength loss.

[0028] (4) Simple and efficient synthesis and application.

[0029] This invention employs a simple polymerization reaction to composite unsaturated acid monomers, unsaturated polyether macromonomers, unsaturated citrate esters, diethylene glycol monovinyl ether, and nano-calcium carbonate. The preparation process is mild, energy-efficient, and highly feasible for industrialization. This system is suitable for large-scale production and can effectively improve concrete performance during on-site construction, particularly demonstrating significant advantages in maintaining fluidity and enhancing early strength. Detailed Implementation

[0030] The present invention will be further described below with reference to embodiments.

[0031] Example 1 (1) Place 1 mol of isopentenyl polyoxyethylene ether (molecular weight 2400) in a reaction flask equipped with a stirring and dropping device, add an appropriate amount of deionized water, and prepare a base solution with a mass concentration of 50%. Start stirring and heat to 40°C to obtain a preheated base solution for later use; mix acrylic acid, triallyl citrate, diethylene glycol monovinyl ether, mercaptoethanol, sodium bicarbonate, ethanol and a certain amount of deionized water to prepare a solution A with a mass concentration of 30%; separately dissolve ammonium persulfate in an appropriate amount of deionized water to prepare a solution B with a mass concentration of 3%; The molar ratio of acrylic acid, isopentenyl polyoxyethylene ether, triallyl citrate, and diethylene glycol monovinyl ether is 2.5:1:0.3:0.5; the amount of mercaptoethanol used is 1.2% of the total mass of acrylic acid, isopentenyl polyoxyethylene ether, triallyl citrate, and diethylene glycol monovinyl ether; the amount of ammonium persulfate added is 1.6% of the total mass of acrylic acid, isopentenyl polyoxyethylene ether, triallyl citrate, and diethylene glycol monovinyl ether; the mass ratio of sodium chloroform to ammonium persulfate is 0.6:1; and the mass ratio of ethanol to triallyl citrate is 1:1. (2) Add solutions A and B simultaneously to the preheated base liquid at 40°C. Maintain the reaction temperature at 40°C. Add solution A at a constant rate for 3.0 hours and solution B at a constant rate for 3.5 hours. After adding solution B, continue to keep the reaction at 40°C for 1.2 hours. After the reaction is complete, cool the system to below 30°C, adjust the pH to 7 with liquid alkali, and finally add deionized water to dilute and obtain a polycarboxylate superplasticizer solution with a solid content of 20 wt.%. (3) Under stirring and 30°C conditions, 45g of nano-calcium carbonate (average particle size of 50nm) was added to 100g of the polycarboxylate superplasticizer solution obtained in step (2), and stirring was continued for 0.8h to obtain early-strength retarded concrete admixture S1.

[0032] Example 2 (1) Place 1 mol of methyl allyl polyoxyethylene ether (molecular weight 2400) in a reaction flask equipped with a stirring and dropping device, add an appropriate amount of deionized water, and prepare a base solution with a mass concentration of 55%. Start stirring and heat to 50°C to obtain a preheated base solution for later use; mix acrylic acid, triallyl citrate, diethylene glycol monovinyl ether, mercaptoacetic acid, sodium bisulfite, ethanol and a certain amount of deionized water to prepare a solution A with a mass concentration of 35%; dissolve ammonium persulfate in an appropriate amount of deionized water to prepare a solution B with a mass concentration of 2%; wherein, acrylic acid, triallyl citrate, diethylene glycol monovinyl ether, mercaptoacetic acid, sodium bisulfite, ethanol and a certain amount of deionized water. The molar ratio of acrylic acid, methyl allyl polyoxyethylene ether, triallyl citrate, and diethylene glycol monovinyl ether is 3.0:1:0.2:0.6; the amount of mercaptoacetic acid is 1.8% of the total mass of acrylic acid, methyl allyl polyoxyethylene ether, triallyl citrate, and diethylene glycol monovinyl ether; the amount of ammonium persulfate is 2.0% of the total mass of acrylic acid, methyl allyl polyoxyethylene ether, triallyl citrate, and diethylene glycol monovinyl ether; the mass ratio of sodium bisulfite to ammonium persulfate is 0.8:1; and the mass ratio of ethanol to triallyl citrate is 2:1. (2) Add solutions A and B simultaneously to a preheated base liquid at 50°C. Maintain the reaction temperature at 50°C. Add solution A at a constant rate for 3.5 hours and solution B at a constant rate for 4.0 hours. After adding solution B, continue to keep the reaction at 50°C for 1.0 hour. After the reaction is complete, cool the system to below 30°C, adjust the pH to 7.5 with liquid alkali, and finally add deionized water to dilute and obtain a polycarboxylate superplasticizer solution with a solid content of 25 wt.%. (3) Under stirring and 20°C conditions, 50g of nano-calcium carbonate (average particle size of 75nm) was added to 100g of the polycarboxylate superplasticizer solution obtained in step (2), and stirring was continued for 1.0h to obtain early-strength retarded concrete admixture S2.

[0033] Example 3 (1) Place 1 mol of isopentenyl polyoxyethylene ether (molecular weight 3000) in a reaction flask equipped with a stirring and dropping device, add an appropriate amount of deionized water, and prepare a base solution with a mass concentration of 60%. Start stirring and heat to 35°C to obtain a preheated base solution for later use; mix acrylic acid, triallyl citrate, diethylene glycol monovinyl ether, mercaptoethanol, sodium bisulfite, ethanol and a certain amount of deionized water to prepare a solution A with a mass concentration of 28%; separately dissolve sodium peroxide in an appropriate amount of deionized water to prepare a solution B with a mass concentration of 1%; wherein, acrylic acid The molar ratio of isopentenyl polyoxyethylene ether, triallyl citrate, and diethylene glycol monovinyl ether is 3.2:1:0.25:0.4; the amount of mercaptoethanol is 1.5% of the total mass of acrylic acid, isopentenyl polyoxyethylene ether, triallyl citrate, and diethylene glycol monovinyl ether; the amount of sodium peroxide added is 2.2% of the total mass of acrylic acid, isopentenyl polyoxyethylene ether, triallyl citrate, and diethylene glycol monovinyl ether; the mass ratio of sodium bisulfite to sodium peroxide is 0.7:1; and the mass ratio of ethanol to triallyl citrate is 1.5:1. (2) Add solutions A and B simultaneously to the preheated base liquid at 35°C. Maintain the reaction temperature at 35°C. Add solution A at a constant rate for 3.2 hours and solution B at a constant rate for 3.8 hours. After adding solution B, continue to keep the reaction at 35°C for 1.5 hours. After the reaction is complete, cool the system to below 30°C, adjust the pH to 8 with liquid alkali, and finally add deionized water to dilute and obtain a polycarboxylate superplasticizer solution with a solid content of 23 wt.%. (3) Under stirring and 25°C conditions, 40g of nano-calcium carbonate (average particle size of 60nm) was added to 100g of the polycarboxylate superplasticizer solution obtained in step (2), and stirring was continued for 0.5h to obtain early-strength retarded concrete admixture S3.

[0034] Comparative Example 1 Without adding triallyl citrate, the other steps are the same as in Example 1, to obtain early-strength retarded concrete admixture PC1.

[0035] Comparative Example 2 Without adding diethylene glycol monovinyl ether, the other steps are the same as in Example 1, to prepare early-strength retarded concrete admixture PC2.

[0036] Comparative Example 3 Without adding nano-calcium carbonate, the other steps are the same as in Example 1, and the early-strength retarded concrete admixture PC3 is prepared.

[0037] Concrete performance tests were conducted according to the national standard GB8076-2008. The tests used reference cement, with zone II medium sand as the fine aggregate, a fineness modulus of 2.6, and a mud content of 0.4%. The coarse aggregate was a two-stage mix (40% 5-10mm and 60% 10-20mm). The reference concrete mix design was cement:sand:aggregate:water = 360:855:965:230. The dosage of polycarboxylate superplasticizer solution in the concrete admixture was set at 0.4% of the cement mass. Concrete performance tests were conducted using the concrete admixtures prepared in Examples 1-3 and Comparative Examples 1-3, respectively. The test results are shown in Table 1.

[0038] Table 1. Test results of concrete performance after incorporating concrete admixtures from Examples 1-3 and Comparative Examples 1-3, respectively.

[0039] As shown in Table 1, the concrete admixtures prepared in Examples 1-3 are superior to those in Comparative Examples 1-3 in terms of water reduction rate, fluidity, slump retention, early and late strength development, and setting time is delayed.

[0040] Comparison between S1 and PC1: PC1 lacks triallyl citrate, resulting in a slump / spread of 180 / 420 mm at 1 hour, which is smaller than S1's 205 / 510 mm. It also has a shorter setting time, and the early strength (1-day and 3-day compressive strength) of PC1 is also lower than that of S1.

[0041] Comparison between S1 and PC2: PC2, lacking diethylene glycol monovinyl ether, exhibited a 1-hour slump / spread of 195 / 450 mm, and 1-day and 3-day compressive strengths of 15.2 MPa and 26.9 MPa, respectively. This indicates that the absence of diethylene glycol monovinyl ether affects the dispersibility of nano-calcium carbonate and fails to effectively guarantee its efficient participation in the cement hydration reaction, thus reducing the early strength of the concrete.

[0042] Comparison of S1 and PC3: PC3 lacks the strength-enhancing mechanism of nano-calcium carbonate, resulting in 1-day and 3-day compressive strengths of 14.6 MPa and 26.0 MPa, respectively, which are lower than the performance indicators of S1 (1-day and 3-day compressive strengths of 16.2 MPa and 28.1 MPa, respectively). This indicates that nano-calcium carbonate, uniformly distributed in the cement matrix, can promote the rapid formation of hydrated calcium silicate gel through seed crystal action, filling pores and significantly improving the density and strength of concrete.

Claims

1. An early-strength retarding concrete admixture, characterized in that... It is made from unsaturated acid monomers, unsaturated polyether macromonomers, unsaturated citrate monomers, unsaturated diethylene glycol monomers, reducing agents, initiators, chain transfer agents, solubilizers, deionized water, and nano-calcium carbonate; wherein the unsaturated citrate monomer is triallyl citrate, and the unsaturated diethylene glycol monomer is diethylene glycol monovinyl ether.

2. The early-strength retarding concrete admixture according to claim 1, characterized in that... The unsaturated acid monomer is acrylic acid.

3. The early-strength retarding concrete admixture according to claim 1, characterized in that... The unsaturated polyether macromonomers are isopentenyl polyoxyethylene ether or methyl allyl polyoxyethylene ether; The structural formula of isopentenyl polyoxyethylene ether is as follows: In the formula, n1 is 25-75; The structural formula of methyl allyl polyoxyethylene ether is as follows: In the formula, n1 is 25-75.

4. The early-strength retarding concrete admixture according to claim 1, characterized in that... The molar ratio of unsaturated acid monomer, unsaturated polyether macromonomer, unsaturated citrate monomer and unsaturated diethylene glycol monomer is 2.5-3.2:1:0.2-0.3:0.4-0.

6.

5. The early-strength retarding concrete admixture according to claim 1, characterized in that... The reducing agent is sodium bisulfite or sodium silicate, and the mass ratio of reducing agent to initiator is 0.6-0.8:1; the initiator is one of sodium peroxide, ammonium persulfate, or hydrogen peroxide, and the amount of initiator is 1.6-2.2% of the total mass of unsaturated acid monomer, unsaturated polyether macromonomer, unsaturated citrate monomer, and unsaturated diethylene glycol monomer; the chain transfer agent is mercaptoacetic acid or mercaptoethanol, and the amount of chain transfer agent is 1.2-1.8% of the total mass of unsaturated acid monomer, unsaturated polyether macromonomer, unsaturated citrate monomer, and unsaturated diethylene glycol monomer.

6. The early-strength retarding concrete admixture according to claim 1, characterized in that... The solubilizer is ethanol, and the mass ratio of solubilizer to unsaturated citrate monomer is 1-2:1; the average particle size of nano-calcium carbonate is 50-75 nm.

7. A method for preparing an early-strength retarded concrete admixture according to any one of claims 1-6, characterized in that... Includes the following steps: (1) Dissolve the unsaturated polyether macromonomer in deionized water to obtain a base solution, and heat the base solution to obtain a preheated base solution; mix the unsaturated acid monomer, unsaturated citrate monomer, unsaturated diethylene glycol monomer, reducing agent, chain transfer agent, solubilizer and deionized water to obtain solution A; dissolve the initiator in deionized water to obtain solution B; (2) Add solution A and solution B dropwise to the preheated bottom liquid at the same time to carry out the reaction. After the dropwise addition is completed, keep the reaction at the temperature, cool down, add liquid alkali to adjust the pH, and then add deionized water to dilute to obtain polycarboxylate superplasticizer solution. (3) Add nano-calcium carbonate to the polycarboxylate superplasticizer solution and stir to obtain an early-strength retarded concrete admixture.

8. The method for preparing the early-strength retarding concrete admixture according to claim 7, characterized in that... In step (1), the mass concentration of the base liquid is 50-60%, and the heating temperature is 35-50℃; the mass concentration of solution A is 28-35%, and the mass concentration of solution B is 1-3%.

9. The method for preparing the early-strength retarding concrete admixture according to claim 7, characterized in that... In step (2), the dropping time of solution A is 3-3.5 hours, and the dropping time of solution B is 3.5-4.0 hours; the reaction temperature is 35-50℃, the holding temperature of the reaction is 35-50℃, and the holding time of the reaction is 1-1.5 hours; the temperature is lowered to below 30℃, and the pH is adjusted to 7-8; the solid content of the polycarboxylate superplasticizer solution is 20-25 wt.%.

10. The method for preparing the early-strength retarding concrete admixture according to claim 7, characterized in that... In step (3), the mass ratio of polycarboxylate superplasticizer solution to nano-calcium carbonate is 1:0.4-0.5, the stirring temperature is 20-30℃, and the stirring time is 0.5-1.0h.

Citation Information

Patent Citations

  • Super-retarding polycarboxylic acid water reducer as well as preparation method and application thereof

    CN119038897A

  • Retarding polycarboxylate superplasticizer and preparation method thereof

    CN119371608A

  • Slow-release early-strengthening polycarboxylate superplasticizer and preparation method thereof

    CN106317342A

  • Super-long slow-release polycarboxylate superplasticizer as well as preparation method and application

    CN113121753A

  • Method for preparing comprehensive polycarboxylic acid water reducing agent from C6 and C5 monomers and prepared water reducing agent

    CN115043988A